Meta Analysis: Effect of Mammography Screening on Breast Cancer Mortality - Bening Rahimi Titisari; Vitri Widyaningsih; Bhisma Murti (Masters Program in Public Health, 2021)
Background: Breast cancer is the most common cancer experienced by women in developing and developed countries. One of the early detection of breast cancer is mammo